Climatic and land cover influences on the spatiotemporal dynamics of Holocene boreal fire regimes. Issue 2 (1st February 2013) - Barrett, Carolyn M.; Kelly, Ryan; Higuera, Philip E.; Hu, Feng Sheng
Abstract : Although recent climatic warming has markedly increased fire activity in many biomes, this trend is spatially heterogeneous. Understanding the patterns and controls of this heterogeneity is important for anticipating future fire regime shifts at regional scales and for developing land management policies. To assess climatic and land cover controls on boreal forest fire regimes, we conducted macroscopic‐charcoal analysis of sediment cores and GIS analysis of landscape variation in south‐central Alaska, USA. Results reveal that fire occurrence was highly variable both spatially and temporally over the past seven millennia. At two of four sites, the lack of distinct charcoal peaks throughout much of this period suggests the absence of large local fires, attributed to abundant water bodies in the surrounding landscape that have likely functioned as firebreaks to limit fire spread. In contrast, distinct charcoal peaks suggest numerous local fires at the other two sites where water bodies are less abundant. In periods of the records where robust charcoal peaks allow identification of local‐fire events over the past 7000 years, mean fire return intervals varied widely with a range of 138–453 years. Furthermore, the temporal trajectories of local‐fire frequency differed greatly among sites and were statistically independent. Inferred biomass burning and mean summer temperature in the region were not significantly correlated prior to 3000 years ago but became positively related subsequently with varying correlation strengths. Climatic variability associated with the Medieval Climate Anomaly and the Little Ice Age, along with the expansion of flammable Picea mariana forests, probably have heightened the sensitivity of forest burning to summer temperature variations over the past three millennia. These results elucidate the patterns and controls of boreal fire regime dynamics over a broad range of spatiotemporal scales, and they imply that anthropogenic climatic warming and associated land cover changes, in particular lake drying, will interact to affect boreal forest burning over the coming decades.